Knowledge for Biology teachers work in Professional Educación (Research, Society and Development, 2020)
The article is the result of a master's dissertation (Morais, 2017) defended within the scope of the Postgraduate Program in Professional Education (PPGEP) and has as its central theme the teaching knowledge. The purpose of the text is to reflect on the teaching knowledge necessary to Biology teachers work in the context of Professional Education (PE). To achieve this goal, we consulted the studies of researchers such as Saviani (1997) Araujo (2008), Moura (2014) and Tardif (2014), which configures the research as bibliographic. The results point to a historical weakness regarding the processes of construction, mobilization and reconstruction of knowledge for teaching in Biology in Basic Education (EB), in general, and in PE, in specific. Knowing this, we discussed a base of knowledge necessary in the daily work of teachers who work with the disciplinary component Biology in EB integrated with EP, namely, the knowledge related to Biology; knowledge related to educational sciences; the researcher's knowledge; experiential knowledge; the knowledge of professional areas in which teachers can work; and critical-contextual and attitudinal knowledge, in order to subsidize teaching work from the perspective of integral human formation.